A Study and Analysis on Feature Extraction in Content-Based Image Retrieval - Nadira, T; Rehna, K; Mon, Fepslin Athish (International Journal of Computer Sciences and Engineering, 2025)
The digital image data is rapidly growing in quantity and heterogeneity. The existing information retrieval techniques does not meet the user’s demand, so there is need to develop an efficient system for content based image retrieval. Content Based Image Retrieval (CBIR) is a technique which uses visual features of image such as color, shape, texture, etc... to search user required image from large annotated image database according to user's requests, in the form of a query image. In this paper we present a study on some technical aspects of current content-based image retrieval systems and feature extraction. Features such as color, shape and texture are analysed to develop a high retrieval accurate cbir system.